Prevalence and Impact of Hypomania Among Night-Shift Healthcare Professionals - Akhtar, Adnan Wajih; Khan, Ahad Kareem; Azeem, Muhammad Kashif; Shahbaz, Ali; Khalil, Maira; Munawar, Asima (Indus Journal of Bioscience Research, 2024)
Objective: This study aimed to investigate the prevalence and impact of hypomanic symptoms among healthcare professionals (HCPs) working night shifts, focusing on behavioral, mental, and physical health outcomes, as well as stimulant use and attitudes toward night shifts. Methods: A cross-sectional study was conducted among HCPs from Shaikh Zayed Hospital, Lahore, using the validated Hypomania Checklist (HCL-32). The survey included questions on demographic and occupational factors, stimulant consumption, and hypomanic symptoms, rated on a five-point Likert scale. Data were analyzed using SPSS version 25 for descriptive and inferential statistics, with p < 0.05 considered significant. Ethical approval was obtained, and participant confidentiality was ensured. Results: Among 200 respondents, 22.5% consumed coffee, 10.5% smoked, and 7.5% used drugs, while alcohol use was low (2%). Positive impacts of night shifts included increased energy (71.5%), confidence (77.5%), and optimism (59.5%). Negative outcomes were significant, with 53.5% reporting exhaustion, 48% irritability, and 49.5% distractibility. Behavioral changes included greater sociability (58%) and a playful personality (70.5%). Conclusion: The findings emphasize the need for structured mental health support and policy interventions to enhance the well-being of HCPs while maintaining high standards of patient care.